Content Marketing Strategy on Social Media to Increase Brand Awareness - Evi Sirait; Iswanto; Ana Yuliana; Yusnia Sinambela; Rizal Perlambang CNAWP (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze content marketing strategies on social media to increase brand awareness. The research method used is a qualitative approach with descriptive methods. Data collection was conducted through interviews, observations, and documentation of marketing activities on social media. The results show that an effective content marketing strategy includes targeted content planning, creative and engaging content creation, consistency in content publication, and active interaction with the audience. Furthermore, utilizing emerging trends on social media can also increase the reach and visibility of content. This strategy has been proven to increase brand awareness because the audience becomes more familiar with and remembers the brand promoted through social media. Therefore, content marketing on social media can be an effective strategy for companies or business actors to strengthen brand image and increase brand recognition among consumers.